Genetic Mapping for Seed Aging Tolerance Under Multiple Environments in Sweet Corn - Yanchao Du; Jianting Lin; Haoxuan Jiang; Huating Zhao; Xuebiao Zhang; Ruigang Wang; Faqiang Feng (Agronomy)
Seed vigor significantly impacts seed production and storage. Enhancing seed vigor is a pivotal goal in sweet corn breeding, as improved seed sowing quality is crucial for agricultural development, aiding in better resilience against storage adversities and facilitating long-term germplasm preservation. In this study, a recombinant inbred line (RIL) population, including 158 families, was derived from the aging-tolerant line K62 and the aging-sensitive line K107. Utilizing SNP arrays, genotypes were identified, and a genetic linkage map was constructed. Composite interval mapping was employed to detect quantitative trait loci (QTLs) associated with five seed vigor traits, namely the seedling fresh weight (SFW), germination potential (GP), germination rate (GR), germination index (GI), and vigor index (VI), at three days after artificial aging treatment. Upon analysis, a total of 42 QTLs affecting seed vigor indices were identified over two years. Of these, six were linked to SFW, while the GP, GR, GI, and VI each comprised nine QTLs. Nine QTL clusters were identified, with significant contributions (>10%) from Loci02.1, Loci05.2, Loci06.1, and Loci10.1, ranging from 9.50% to 24.20%, 8.89% to 11.54%, 9.16% to 15.55%, and 7.54% to 17.77%, respectively. Candidate genes were explored within QTL cluster regions based on the aging-induced transcriptomic sequencing data of K62 and K107. Through Gene Ontology enrichment, gene annotation, and expression profiling clustering analyses, 12 positive candidate genes linked to seed aging tolerance were identified. This study provides a foundational understanding of the genetic mechanisms of seed aging tolerance and the innovation of an elite germplasm for seed aging tolerance in sweet corn.